Profound T Lymphocyte and DNA Repair Defect Characterizes Schimke Immuno-Osseous Dysplasia - Vladyka, Ondřej; Zieg, Jakub; Pátek, Ondřej; Bloomfield, Markéta; Paračková, Zuzana; Šedivá, Anna; Klocperk, Adam (Journal of clinical immunology, 2024)
Schimke immuno-osseous dysplasia is a rare multisystemic disorder caused by biallelic loss of function of the SMARCAL1 gene that plays a pivotal role in replication fork stabilization and thus DNA repair. Individuals affected from this disease suffer from disproportionate growth failure, steroid resistant nephrotic syndrome leading to renal failure and primary immunodeficiency mediated by T cell lymphopenia. With infectious complications being the leading cause of death in this disease, researching the nature of the immunodeficiency is crucial, particularly as the state is exacerbated by loss of antibodies due to nephrotic syndrome or immunosuppressive treatment. Building on previous findings that identified the loss of IL-7 receptor expression as a possible cause of the immunodeficiency and increased sensitivity to radiation-induced damage, we have employed spectral cytometry and multiplex RNA-sequencing to assess the phenotype and function of T cells ex-vivo and to study changes induced by in-vitro UV irradiation and reaction of cells to the presence of IL-7. Our findings highlight the mature phenotype of T cells with proinflammatory Th1 skew and signs of exhaustion and lack of response to IL-7. UV light irradiation caused a severe increase in the apoptosis of T cells, however the expression of the genes related to immune response and regulation remained surprisingly similar to healthy cells. Due to the disease's rarity, more studies will be necessary for complete understanding of this unique immunodeficiency.
Keywords: arterioskleróza; mužské pohlaví; Arteriosclerosis; Ultraviolet Rays; Male; DNA Repair; Immunodeficiency; Osteochondrodysplasias; Nephrotic Syndrome; Apoptosis; Humans; Female; DNA Helicases; primární imunodeficience; Lymphopenia; Immunologic Deficiency Syndromes; Thymus; lidé; Exhaustion; Bone Diseases, Metabolic; Peritoneal dialysis; Growth Disorders; ženské pohlaví; nefrotický syndrom; T-Lymphocytes; Cytometry; syndromy imunologické nedostatečnosti; metabolické nemoci kostí; poruchy růstu; Child; dítě; T-lymfocyty; DNA-helikasy; Primary Immunodeficiency Diseases; IL-7; Schimke Imunoosseous dysplasia; apoptóza; Pulmonary Embolism; ultrafialové záření; RNA-seq; oprava DNA; Schimke immuno-osseous dysplasia; Spectral Cytometry; SIOD; osteochondrodysplazie; T cell; plicní embolie